THE ROLE OF HEALTH BELIEFS IN COVID-19 PREVENTIVE BEHAVIOR - Manusyan , S.H.; Hakobjanyan, A.R. (Modern Psychology, 2021)
Beliefs have proved to be significant factors in regulating behavior, including health-related behaviors. The health belief model suggests that people can perform or change their behavior depending on their perceptions of health and disease. The present study discusses the health beliefs underlying Covid-19 preventive behaviors. The study objectives were to identify the predictive significance of health- related beliefs in COVID-19 preventive behavior as well as to content-wise interpret the specifics of some COVID-19-related beliefs and self-reported behavior. The sample comprised 237 participants (64,1% female, M=29,75; SD=10,693; Range=18-58), regression analysis was performed. Some results of in-depth interviews on COVID-19 perceptions (conducted as part of the project’s qualitative component) were thematically analyzed and used in interpreting the statistical data. According to the results, preventive behaviors such as frequent hand washing or disinfection of frequently used objects, infrequent leaving the house, wearing a mask, avoiding meeting friends and relatives are conditioned by beliefs about the effectiveness of preventive behavior, perceived barriers and perceived severity. The predictive significance of beliefs for COVID-19 preventive behaviors suggests that their further identification and scrutiny can contribute to the improvement and promotion of individuals’ preventive behaviors both in times of the pandemic and other large-scale healthcare issues.
Keywords: Covid-19; preventive behavior; health beliefs; regression analysis